Factors affecting the efficiency of in vitro regeneration from seedling-derived nodal explants of Nyctanthes arbor-tristis L. and evaluation of genetic fidelity - Kumar Mishra A.; Nath Tiwari K.; Mishra P.; Kumar Tiwari S.; Kumar Mishra S.; Singh J. (My University, 2025)
An in vitro micropropagation protocol for Nyctanthes arbor-tristis was developed through the culture of seedling-derived nodal explants. The highest direct shoot induction rate, the mean number of shoots per explant and average shoot length was obtained on MS medium supplemented with 5 mg/l 6-benzylaminopurine (BAP). Full-strength MS medium was found better than other concentrations for organogenesis. Their lower or higher concentration from optimum level was inhibitory for shoot regeneration. Among different carbon sources tested for organogenesis, MS medium supplemented with 87.64 mM sucrose was superior to other carbon sources for in vitro morphogenesis. Best rooting of microshoots was achieved on one-quarter strength MS medium supplemented with 2 mg/l indole-3-butyric acid (IBA). Under this treatment, maximum mean number of roots/shoot and mean root length were 9.40 ± 0.70 and 2.47 ± 0.25 cm, respectively. The genetic fidelity among regenerates and donor plant has been confirmed by ISSR markers. © 2019, © 2019 Societá Botanica Italiana.